(untitled) (Italian Journal of Public Health, 2012)
Venous thromboembolism (VTE) is a condition in which a thrombus (a solid mass of blood constituents) forms in a vein. VTE represents an extremely common medical problem manifested as either deep venous thrombosis (DVT) or pulmonary embolism (PE) affecting apparently healthy as well as hospitalized patients. Often PE is the physiopathological consequence of the DVT of low extremities vessels, in particular of the calve......